Empirical Evidence of ESG Disclosure's Impact on Corporate Investment Decision in Indonesia - Cahyono, Suham; Damayanti, Vira Ayu; Ardianto, Ardianto (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
The purpose of this study is to investigate the impact of environmental, social, and governance (ESG) disclosure on corporate investment decisions. Data were collected from annual reports of firms listed in Indonesia Stock Exchange between 2015 and 2020 (378 firm-year observations). Using Ordinary Least Square (OLS) and fixed effect estimation, this study found that the dimension of ESG practices positively affects corporate investment decisions. In addition, the presidential election periods increase the effectiveness of corporate investment decisions. The study results reveal that uncertainty in the economic and business environment over the impact of general elections increases the company's ability to generate higher investments. This study contributes to the company strategic alignment to justify management about investment prioritize in the stakeholder wealth through ESG disclosure.